2017
DOI: 10.1021/jacs.7b01209
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Macrocycles for Organic Rechargeable Batteries

Abstract: Organic rechargeable batteries, composed of redox-active molecules, are emerging as candidates for the next generation of energy storage materials because of their large specific capacities, cost effectiveness, and the abundance of organic precursors, when compared with conventional lithium-ion batteries. Although redox-active molecules often display multiple redox states, precise control of a molecule's redox potential, leading to a single output voltage in a battery, remains a fundamental challenge in this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 52 publications
1
85
0
Order By: Relevance
“…Rings composed of phenylenediimide and cyclohexyl moieties were likewise studied as active materials. Here, the performance of the cell depends strongly on the extent of the formed rings . In comparison to phenylenediimide, naphthalenediimide (NDI) possesses a larger aromatic system and a lower ring strain within the imide moieties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rings composed of phenylenediimide and cyclohexyl moieties were likewise studied as active materials. Here, the performance of the cell depends strongly on the extent of the formed rings . In comparison to phenylenediimide, naphthalenediimide (NDI) possesses a larger aromatic system and a lower ring strain within the imide moieties.…”
Section: Methodsmentioning
confidence: 99%
“…Here, the performance of the cell depends strongly on the extento ft he formed rings. [66] In comparison to phenylenediimide, naphthalenediimide (NDI) possessesalarger aromatic system and al ower ring strain within the imide moieties. Thus, NDIs are usually more stable and more often used as active battery material.…”
Section: Diimidesand Dianhydridesmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] Several cathodes materials,s uch as copper hexacyanoferrate, [20] V 2 O 5 , [21,22] and MnO 2 , [23,24] have been coupled with the zinc anode to form the rechargeable aqueous zinc batteries.I nt hese reports,c athodes still involve toxic and/or environmentally unfriendly elements in their components.V ery recently,o rganic electrode materials have been considered as the low-toxicity and sustainable alternative to conventional inorganic electrode materials. [25][26][27][28][29][30][31][32][33][34][35][36] In theory,the combination of organic cathode and zinc anode in mild electrolyte should be ap romising approach for developing low toxic battery,b ecause some organics show very limited toxicity.However,the academic results on this topic are rarely reported. Only very recently,C hen et al first reported an aqueous zinc battery using aq uinone (C4Q)-cathode,w hich shows ah igh energy density.…”
mentioning
confidence: 99%
“…Moreover, other chemistries have also been developed based on the structures of perylene and naphthalenediimide . In summary, n‐type organic molecules have been investigated widely, resulting in a large variety of compounds that have been tested in the Li‐ion RFB system.…”
Section: Organic Redox Shuttles In Lithium‐ion Rfbsmentioning
confidence: 99%